Recent Advances in Pharmacological Intervention of Osteoarthritis: A Biological Aspect - Deng, Jinxia; Zong, Zhixian; Su, Zhanpeng; Chen, Haicong; Huang, Jianping; Niu, Yanru; Zhong, Huan; Wei, Bo (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is a degenerative joint disease in the musculoskeletal system with a relatively high incidence and disability rate in elderly. It is characterized by the degradation of articular cartilage, inflammation of the synovial membrane, abnormal structure in the periarticular and subchondral bones. Although progress has been made in uncovering the molecular mechanism, the pathogenesis of OA is still complicated and unclear. Nevertheless, there is no treatment method that can effectively prevent or reverse the deterioration of cartilage and bone structure. Recent years, in the field of pharmacology, research focus has shifted to disease prevention and early treatment of OA. Biological reagents become more and more attractive choices as their direct or indirect biological functions in the treatment of OA. From the pharmacological aspect, stem cell therapy is a very special technique which is not included in this review. We searched for key words such as osteoarthritis, DNA, RNA, exosomes, platelet-rich plasma (PRP), protein, gene, etc. The literatures ranging from January 2016 to August 2021 were included and summarized. In this review, we aim to help readers have a complete and precise understanding of the current pharmacological research progress in the intervention of OA from the biological aspect and provide an indication for the future clinical studies.